Synchrony of Protein and Energy in The Rumen to Maximize The Production of Microbial Protein - Simon P Ginting (Indonesian Center for Animal Research and Development, 2005)
Justification for continued use of ruminants for competitive meat production reside in I) their ability to hydrolyse structural carbohydrate (not used by non ruminant animals) as a source of energy, 2) their ability to transform non protein nitrogen substances into ruminal microbial protein, and 3) their ability to use microbial protein as their main protein sources for production . Through fermentation in the rumen, microbial protein supply 70-100 percent of total protein available and 70-85 percent of energy to the animal . Therefore, the role of efficient rumen fermentation to yield microbial protein is vital to the ruminants . Fermentation efficiency does not only depend on the nutrient contents of the diets, but is strongly influenced by the rate of degradation of the nutrients in the rumen, particularly protein and carbohydrate (CHO) . Significant improvement in the fermentation efficiency could be achieved when protein and energy (CI-IO) degradations occur in harmony (synchrony) during the fermentation period . The Cornell system could be used in accommodating the synchrony of protein and energy degradation in ration formulation . For this, fractionation of CHO and protein based on their degradability is required . This system fractionates the CFIO into fraction A (fastly degraded), fraction B I ( intermediate), fraction B2 (slowly degraded) and fraction C (not degraded) . The same fractionation is applied to protein nainely fraction A (soluble ; non protein nitrogen), fraction B t (soluble protein), fraction B2 (mostly degradable protein), fraction B3 (not degradable protein) and fraction C (not available protein) . Alternatively, synchronization of protein and CHO degradation in ration formulation could use Synchronization Index (SI) as an i ndicator . S I describes the ratio between the degradation of N and organic matter (OM) or CHO . St of 1 .0 indicates perfect synchrony, while SI<1 .0 indicates the degree of asynchrony . Data on the degradation rate of protein and CHO of agricultural wastes or by-products as well as agroindustry by-products in Indonesia is very limited . It is urged to develop the data base on these degradation characteristics in order to fully use the phenomenon of protein and energy synchrony to formulate rations based on the locally available feedstuffs . Key words : Synchronization, energy . protein, fermentation, efficiency